Magnetocaloric effects in the prototype spin crossover complex [Fe(L)2](BF4)2 in pulsed magnetic fields - Klara Lünser; Catalina Salazar Mejía; Tino Gottschall; Kübra Gürpinar; Orhan Atakol; Eyüp Kavak; Baris Emre; Enric Stern-Taulats; Lluís Mañosa (APL Materials)
Spin crossover (SCO) complexes have been shown to exhibit giant mechanocaloric effects. Due to the change of magnetization at the spin crossover transition, they are also expected to show magnetocaloric effects. However, experimental studies on the magnetocaloric properties in SCOs are scarce. Here, we have studied the magnetocaloric response in the SCO complex [Fe(L)2](BF4)2, [L = 2,6-di(pyrazol-1-yl)pyridine] using pulsed magnetic fields. We show that applying a magnetic field can induce a partial transformation from the low spin to the high spin state. We directly measure the adiabatic temperature change of the transformation for different initial sample temperatures and magnetic fields and compare them with calculations using the Clausius–Clapeyron equation. While we found a large change in entropy of 70 J kg−1 K−1 at 50 T, the corresponding temperature change of 1.5 K is small due to the weak dependence of the transformation temperature on the magnetic field. Our study enhances the knowledge of caloric effects in SCO complexes, which so far have mainly focused on mechanocaloric studies.